Preparation method of iron-cobalt doped porous carbon nanofiber and application thereof

CN116666657BActive Publication Date: 2026-10-09HEFEI UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310632674.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-31
Publication Date
2026-10-09
Estimated Expiration
2043-05-31

AI Technical Summary

Technical Problem

[0005]为解决现有过渡金属掺杂的碳纳米结构氧还原电催化剂普遍存在的催化位点少、催化活性低的问题,本发明提供一种具有较大的比表面积和较多的活性位点的铁钴掺杂多孔碳纳米纤维的制备方法,以提高其电催化性能

Benefits of technology

[0024]The iron-cobalt-doped porous carbon nanofibers prepared in this invention can be used as a catalyst in the electrocatalytic oxygen reduction process, such as in the fabrication of an oxygen reduction reaction electrode. The electrode is a glassy carbon electrode coated with the aforementioned iron-cobalt-doped porous carbon nanofiber material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116666657B_ABST
    Figure CN116666657B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of iron-cobalt doped porous carbon nanofibers and application thereof, and is characterized in that FeCo-MOFs and ZIF-8 MOFs are assembled into electrospun nanofibers, and then iron-cobalt doped porous carbon nanofibers are obtained through calcination, wherein the FeCo-MOFs serve as a main providing source of the dual components, the ZIF-8 is evaporated after pyrolysis and leaves a large number of pore structures, and the synergistic effect between the dual components can effectively improve the catalytic effect of the catalyst, and the large number of pore structures can provide a larger specific surface area for the material, so that more active sites are formed. Therefore, the iron-cobalt doped porous carbon nanofiber material has more excellent electrocatalytic performance, and the preparation method has the advantages of low raw material price and simple operation, and can be mass-produced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of functional nanomaterials, specifically relating to a nanofiber electrocatalytic material for oxygen reduction processes in electrocatalysis. Background Technology

[0002] Fuel cells have attracted much attention as a potential alternative to traditional fossil fuels. The oxygen reduction reaction (ORR) is crucial for fuel cells, but commercially available electrocatalysts are mostly precious metals, such as platinum-carbon and ruthenium dioxide. However, the cost, stability, and abundance of these catalysts limit their development prospects. Therefore, developing high-performance ORR catalysts is essential. Nanostructured materials, due to their unique properties, have long been considered an effective alternative to traditional precious metals.

[0003] Transition metal-doped carbon nanomaterials have gained attention in the field of electrocatalysis due to their performance and stability, which are comparable to traditional noble metal catalysts. Nanomaterials primarily doped with iron and cobalt have also proven to be reliable catalytic materials. Existing iron-cobalt-doped nanomaterials are often prepared by immobilizing them in a metal-organic framework and then pyrolyzing them, or by doping metals into a decomposable template. However, these methods generally have some drawbacks. For example, during pyrolysis, metal atoms in these metal-doped catalysts tend to aggregate, leading to a reduction in catalytic active sites. Furthermore, it is difficult for all active sites in these materials to be exposed to participate in the catalytic process, ultimately resulting in low catalytic activity.

[0004] Therefore, the current need in the field of electrocatalysis is to find a transition metal-doped carbon nanostructure catalyst with highly dispersed metal atoms, a large number of catalytic sites, and low preparation cost. Summary of the Invention

[0005] To address the common problems of limited catalytic sites and low catalytic activity in existing transition metal-doped carbon nanostructured oxygen reduction electrocatalysts, this invention provides a method for preparing iron-cobalt-doped porous carbon nanofibers with a large specific surface area and numerous active sites, thereby improving their electrocatalytic performance.

[0006] To solve the technical problem, the present invention adopts the following technical solution:

[0007] A method for preparing iron-cobalt doped porous carbon nanofibers, characterized by comprising the following steps:

[0008] (1) FeCo-MOFs were prepared by hydrothermal method in a mixed solvent of methanol and deionized water; ZIF-8MOFs were prepared by mixing 2-methylimidazolium and zinc salt at room temperature;

[0009] (2) Disperse FeCo-MOFs and ZIF-8MOFs in N,N-dimethylformamide, then add polyacrylonitrile and stir evenly to form a spinning solution;

[0010] (3) The obtained spinning solution is spun to obtain a polyacrylonitrile fiber film of FeCo-MOFs@ZIF-8MOFs;

[0011] (4) The obtained fiber film was calcined in an inert gas atmosphere to obtain iron-cobalt doped porous carbon nanofibers.

[0012] Electrospinning technology can produce uniform fiber materials and allows for flexible doping with various metals and other heteroatoms. Bimetallic organic frameworks (MOFs) leave two-component active sites after pyrolysis, and the synergistic effect between these two active sites enhances catalytic activity. Furthermore, different types of MOFs produce different pore structures after pyrolysis; adjusting the ratio of different MOFs can effectively regulate the microstructure and active sites of the derived material, thereby improving its catalytic performance. The generation of defects in bimetallic nanomaterials and the synergistic effect between the two metals can enhance catalytic activity. Therefore, this invention provides a method for preparing iron-cobalt-doped porous carbon nanofibers, mainly comprising: assembling two MOFs into nanofibers via electrospinning, followed by pyrolysis to prepare porous carbon nanofiber materials. The framework structure and the hierarchical structure of the fibers result in more pores between the metal nanoparticles, alleviating the problem of metal nanoparticle aggregation caused by pyrolysis. Simultaneously, the two MOFs have different pore structures and compositions; during pyrolysis, the volatilization of organic matter and zinc elements constructs a hierarchical pore structure, increasing the specific surface area of ​​the material and facilitating the exposure of active sites. In summary, this preparation method is low-cost, and the resulting product has a high specific surface area, a hierarchical porous structure, and more active sites, which can significantly improve catalytic performance.

[0013] Specifically, in view of the shortcomings of the existing technology, the present invention provides the following technical solution:

[0014] A method for preparing iron-cobalt doped porous carbon nanofibers, characterized by comprising the following steps:

[0015] (1) FeCo-MOFs were prepared by hydrothermal method in a mixed solvent of methanol and deionized water; ZIF-8MOFs were prepared by mixing 2-methylimidazolium and zinc salt at room temperature;

[0016] (2) Disperse FeCo-MOFs and ZIF-8MOFs in N,N-dimethylformamide, then add polyacrylonitrile and stir evenly to form a spinning solution;

[0017] (3) The obtained spinning solution is spun to obtain a polyacrylonitrile fiber film of FeCo-MOFs@ZIF-8MOFs;

[0018] (4) The obtained fiber film was calcined in an inert gas atmosphere to obtain iron-cobalt doped porous carbon nanofibers.

[0019] Further, the preparation method of the FeCo-MOFs is as follows: F127 is dissolved in deionized water, iron salt and cobalt salt are added and stirred evenly, then acetic acid is added, followed by 2-aminoterephthalic acid dissolved in methanol, and stirred evenly to obtain a reaction solution; the reaction solution is subjected to hydrothermal reaction at 100-140℃ for 18-28h (preferably at 110℃ for 24h) to obtain FeCo-MOFs; in the reaction solution: methanol and The volume ratio of deionized water is 1:1, the concentration of F127 is 0.016-0.042 g / mL, the concentration of iron salt is 0.005-0.0065 g / mL (preferably 0.006 g / mL), the concentration of cobalt salt is 0.0055-0.0065 g / mL (preferably 0.0064 g / mL), the concentration of 2-aminoterephthalic acid is 0.004 g / mL, and the volume ratio of acetic acid to deionized water is 1:80. The iron salt is preferably ferric chloride hexahydrate, and the cobalt salt is preferably cobalt nitrate hexahydrate.

[0020] Further, the ZIF-8MOFs are prepared by dissolving 2-methylimidazole in methanol, adding zinc salt, stirring at room temperature, and then centrifuging. The molar ratio of zinc salt to 2-methylimidazole is 1:3-6. The zinc salt is preferably zinc nitrate hexahydrate.

[0021] Further, in step (2), the ratio of polyacrylonitrile, N,N-dimethylformamide, FeCo-MOFs and ZIF-8-MOFs is 0.15-0.25g:3mL:0.15-0.2g:0.05-0.2g, preferably 0.2g:3mL:0.2g:0.15g.

[0022] Furthermore, in step (3), the spinning voltage is 13-17kV (preferably 15kV), and the distance from the spinning needle to the collecting copper mesh is 10-20cm (preferably 15cm).

[0023] Furthermore, in step (4), the inert gas used is nitrogen. The calcination is divided into two steps: first, the temperature is raised to 200-300℃ and kept at that temperature for 1-3 hours, and then the temperature is raised to 800-100℃ and kept at that temperature for 2-4 hours.

[0024] The iron-cobalt-doped porous carbon nanofibers prepared in this invention can be used as a catalyst in the electrocatalytic oxygen reduction process, such as in the fabrication of an oxygen reduction reaction electrode. The electrode is a glassy carbon electrode coated with the aforementioned iron-cobalt-doped porous carbon nanofiber material.

[0025] The beneficial effects of this invention are reflected in:

[0026] This invention assembles FeCo-MOFs and ZIF-8MOFs into electrospun nanofibers, followed by calcination to obtain iron-cobalt-doped porous carbon nanofibers. FeCo-MOFs serve as the primary source of the two components, while ZIF-8 is evaporated after pyrolysis, leaving behind a large number of porous structures. The synergistic effect between the two components effectively enhances the catalytic effect of the catalyst, and the abundant porous structures provide a larger specific surface area, thereby forming more active sites. Therefore, the iron-cobalt-doped porous carbon nanofiber material of this invention exhibits superior electrocatalytic performance, and the preparation method of this invention has the advantages of low raw material cost and simple operation, enabling large-scale production. Attached Figure Description

[0027] Figure 1 The image shows a transmission electron microscope (TEM) image of the FeCo-MOFs obtained in Example 1.

[0028] Figure 2 The image shows a transmission electron microscope (TEM) image of the ZIF-8MOFs obtained in Example 1.

[0029] Figure 3 This is a scanning electron microscope image of the polyacrylonitrile nanofibers of FeCo-MOFs@ZIF-8MOFs obtained in Example 1.

[0030] Figure 4 This is a scanning electron microscope image of the iron-cobalt doped porous carbon nanofiber material obtained in Example 1.

[0031] Figure 5 This is a transmission electron microscope (TEM) image of the iron-cobalt-doped porous carbon nanofiber material obtained in Example 1.

[0032] Figure 6 The image shows the XRD pattern of the iron-cobalt doped porous carbon nanofiber material obtained in Example 1.

[0033] Figure 7 This is a transmission electron microscope (TEM) image of the iron-cobalt-doped porous carbon nanofiber material obtained in Comparative Example 1.

[0034] Figure 8 This is a transmission electron microscope (TEM) image of the iron-cobalt-doped porous carbon nanofiber material obtained in Comparative Example 2.

[0035] Figure 9 This is a transmission electron microscope (TEM) image of the iron-cobalt-doped porous carbon nanofiber material obtained in Comparative Example 3.

[0036] Figure 10 This is a transmission electron microscope (TEM) image of the iron-cobalt-doped porous carbon nanofiber material obtained in Comparative Example 4.

[0037] Figure 11 This is a transmission electron microscope (TEM) image of the iron-cobalt-doped porous carbon nanofiber material obtained in Comparative Example 5.

[0038] Figure 12 The LSV curves of the nanofiber materials obtained in Example 1 and Comparative Examples 1-6 are shown. Detailed Implementation

[0039] The embodiments of the present invention will be described in detail below. The following embodiments are implemented based on the technical solution of the present invention, and detailed implementation methods and specific operation processes are given. However, the protection scope of the present invention is not limited to the following embodiments.

[0040] Unless otherwise specified, the experimental methods used in the following examples are conventional methods; unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0041] Information on the instruments used in the following embodiments is shown in the table below:

[0042] Table 1 Instrument Information Sheet

[0043] Electric constant temperature drying oven DHG-9011A Shanghai Jinghong Experimental Equipment Co., Ltd. Multi-point magnetic stirrer RT10 Guangzhou Yike Laboratory Technology Co., Ltd. spinning machine KI-602 Beijing Keli Jianyuan Nabertherm RTCH 80-450 / 15 Germany Scanning electron microscope Zeiss Supra 40 Carl Zeiss, Germany Transmission electron microscope JEOL-F2010 Hitachi, Japan AUTOLLAB Electrochemical Workstation PGSTAT302N MassMutual GmbH

[0044] Example 1

[0045] In this embodiment, the preparation process of iron-cobalt doped porous carbon nanofibers is as follows:

[0046] (1) Weigh 0.64g F127 and dissolve it in 15mL of deionized water. Add 0.179g ferric chloride hexahydrate and 0.193g cobalt nitrate hexahydrate and stir until homogeneous. Then add 375μL of acetic acid and 0.12g 2-aminoterephthalic acid dissolved in 15mL of methanol. Stir for 2h to obtain the reaction solution. Pour the reaction solution into a 40mL reaction vessel and perform hydrothermal reaction at 110℃ for 24h. After cooling, wash with deionized water to obtain FeCo-MOFs.

[0047] 1.375 g of 2-methylimidazole was dissolved in 62.5 mL of methanol solution and stirred until homogeneous. 1.2 g of zinc nitrate hexahydrate was weighed, dissolved in 50 mL of methanol solution, and quickly poured into the above solution. The mixture was stirred for 2 h and washed with ethanol to obtain ZIF-8MOFs.

[0048] (2) Weigh 0.2g of FeCo-MOFs and 0.15g of ZIF-8MOFs and disperse them in 3mL of N,N-dimethylformamide solution. After sonication for 40min, add 0.2g of polyacrylonitrile and stir for 12h to prepare spinning solution.

[0049] (3) The obtained spinning solution is drawn into the syringe of the spinning machine. The distance between the needle and the collection net is 15cm, the spinning voltage is 15kV, the spinning syringe speed is 0.3mL / h, and the spinning film is collected once every two hours.

[0050] (4) The obtained FeCo-MOFs@ZIF-8MOFs polyacrylonitrile nanofiber film was calcined under an inert gas: first, the temperature was raised to 260℃ at a heating rate of 1℃ / min and held for 2h under a nitrogen atmosphere, and then the temperature was raised to 900℃ at a heating rate of 5℃ / min and held for 3h. After grinding the product, the iron-cobalt doped porous carbon nanofiber material was obtained.

[0051] The reaction mechanism in this embodiment is as follows: two types of small-sized MOF particles are installed into fibers using electrospinning technology. At high temperatures, the organic matter evaporates, leaving only metal and nitrogen- and carbon-doped nanofiber materials. Since zinc evaporates at 900℃, many micropores are left on the fiber surface, which directly increases the specific surface area of ​​the fiber material. Simultaneously, the ZIF-8 framework also contains a large amount of nitrogen, which directly increases the nitrogen source for the spun fibers. Finally, iron-cobalt-doped porous carbon nanofiber materials are produced.

[0052] Figure 1 The image shows the transmission spectrum of the FeCo-MOFs particles obtained in this embodiment. It can be seen that the overall structure is a long rod shape, with a length of about 100 nm and a width of about 50 nm.

[0053] Figure 2 The image shows the transmission spectrum of the ZIF-8MOFs particles obtained in this embodiment. It can be seen that the overall structure is relatively uniform, the morphology is a dodecahedral structure, and the size is about 100nm.

[0054] Figure 3 The image shows a scanning electron microscope (SEM) image of the FeCo-MOFs@ZIF-8MOFs polyacrylonitrile nanofibers obtained in this embodiment. It can be seen that the spinning surface is relatively rough, mainly due to the roughness caused by the incorporation of two types of MOFs particles.

[0055] Figure 4 The image shown is a scanning electron microscope image of the iron-cobalt doped porous carbon nanofiber material obtained in this embodiment. It can be seen that the main morphology of the fibrous spun fibers after calcination is a thin rod shape with many small pore structures on the surface.

[0056] Figure 5The image shown is a transmission electron microscope (TEM) image of the iron-cobalt doped porous carbon nanofiber material obtained in this embodiment. It can be clearly seen that the rod-shaped structure exhibits many pore structures of different sizes, which is mainly caused by the volatilization of organic matter and zinc in the spun fibers.

[0057] Figure 6 The XRD pattern of the iron-cobalt doped porous carbon nanofiber material obtained in this embodiment shows that its composition is iron carbide and cobalt (Fe3C / Co).

[0058] Comparative Example 1

[0059] This comparative example prepared iron-cobalt-doped porous carbon nanofibers using a similar method to Example 1. The difference was that ZIF-8MOFs were not doped in the spinning solution. Specifically, step (2) was as follows: 0.2g of FeCo-MOFs were weighed and dispersed in 3mL of N,N-dimethylformamide solution. After sonication for 40min, 0.2g of polyacrylonitrile was added and stirred for 12h to prepare the spinning solution.

[0060] Figure 7 The image shown is a transmission electron microscope (TEM) image of the iron-cobalt-doped porous carbon nanofibers obtained in this embodiment. It can be seen that FeCo-MOF is uniformly embedded in the pore structure left after the spinning fibers are calcined.

[0061] Comparative Example 2

[0062] This comparative example prepared iron-cobalt-doped porous carbon nanofibers using a similar method to Example 1, except that the amount of ZIF-8MOF used in step (2) was 0.05g.

[0063] Figure 8 The image shown is a transmission electron microscope (TEM) image of the iron-cobalt doped porous carbon nanofibers obtained in this embodiment. It can be seen that after adding less ZIF-8MOF, some larger pores remain in the spun fibers after calcination.

[0064] Comparative Example 3

[0065] This comparative example prepared iron-cobalt-doped porous carbon nanofibers using a similar method to Example 1, except that the amount of ZIF-8MOF used in step (2) was 0.1g.

[0066] Figure 9 The image shown is a transmission electron microscope (TEM) image of the iron-cobalt doped porous carbon nanofibers obtained in this embodiment. It can be seen that the increase in ZIF-8MOF leads to an increase in the number of macropores.

[0067] Comparative Example 4

[0068] This comparative example prepared iron-cobalt-doped porous carbon nanofibers using a similar method to Example 1, except that 0.238 g of ferric chloride hexahydrate and 0.128 g of cobalt nitrate hexahydrate were added in step (1).

[0069] Figure 10 The image shown is a transmission electron microscope (TEM) image of the iron-cobalt-doped porous carbon nanofibers obtained in this embodiment. It can be seen that the FeCo-MOFs particles prepared with the iron-cobalt ratio in this comparative example will leave larger particles after calcination.

[0070] Comparative Example 5

[0071] This comparative example prepared iron-cobalt-doped porous carbon nanofibers using a similar method to Example 1, except that 0.119 g of ferric chloride hexahydrate and 0.256 g of cobalt nitrate hexahydrate were added in step (1).

[0072] Figure 11 The image shown is a transmission electron microscope (TEM) image of the iron-cobalt-doped porous carbon nanofibers obtained in this embodiment. It can be seen that the FeCo-MOFs particles prepared with the iron-cobalt ratio in this comparative example will break into some fibers after calcination.

[0073] Comparative Example 6

[0074] This comparative example uses commercial platinum-carbon as the electrode material.

[0075] The electrocatalytic performance of the iron-cobalt doped porous carbon nanofibers obtained in the above examples and comparative examples was tested as follows: Electrochemical tests were performed using a three-electrode system on an electrochemical workstation. The working electrode was a glassy carbon disk electrode with a diameter of 5 mm (disk area 0.196 cm²). 2 The reference electrode was an Ag / AgCl electrode, and the counter electrode was a carbon rod electrode. 5 mg of the obtained nanofibers were dispersed in 490 μL of ethanol, and 10 μL of naphthol solution was added. The mixture was sonicated for 3 hours, and then 15 μL was applied to the glassy carbon surface using a microsyringe. Before testing, O2 was bubbled into the electrolyte (0.1 M KOH solution) for at least half an hour to saturate the electrolyte with O2. During the test, the rotating disk electrode was set to 1600 rpm, the scan rate to 5 mV / s, and the test voltage to be -1 to 0.1 V (Ag / AgCl). The CV curve was tested for ten cycles before testing the catalyst performance.

[0076] Figure 12 The LSV curves of the samples obtained in each embodiment and comparative example show that the half-wave potential of the target product obtained in Example 1 is 0.88V, which is higher than that of the other comparative examples (the half-wave potentials of the products obtained in Comparative Examples 1 to 6 are 0.84V, 0.86V, 0.87V, 0.82V, 0.86V, and 0.85V, respectively). Therefore, assembling a bimetallic organic framework structure in electrospun fibers can effectively improve the electrocatalytic performance of the material.

[0077] The above are merely exemplary embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing iron-cobalt-doped porous carbon nanofibers, characterized in that, Includes the following steps: (1) FeCo-MOFs were prepared in a mixed solvent of methanol and deionized water using a hydrothermal method; ZIF-8MOFs were prepared by mixing 2-methylimidazolium and zinc salt at room temperature; (2) Disperse FeCo-MOFs and ZIF-8MOFs in N,N-dimethylformamide, then add polyacrylonitrile and stir evenly to form a spinning solution; (3) The obtained spinning solution was spun to obtain a polyacrylonitrile fiber film of FeCo-MOFs@ZIF-8MOFs; (4) The obtained fiber film was calcined in an inert gas atmosphere to obtain iron-cobalt doped porous carbon nanofibers.

2. The preparation method according to claim 1, characterized in that, The preparation method of FeCo-MOFs is as follows: F127 is dissolved in deionized water, iron salt and cobalt salt are added and stirred evenly, then acetic acid is added, and then 2-aminoterephthalic acid dissolved in methanol is added and stirred evenly to obtain a reaction solution; the reaction solution is subjected to hydrothermal reaction at 100-140℃ for 18-28h to obtain FeCo-MOFs. In the reaction solution: the volume ratio of methanol to deionized water is 1:1, the concentration of F127 is 0.016-0.042 g / mL, the concentration of iron salt is 0.005-0.0065 g / mL, the concentration of cobalt salt is 0.0055-0.0065 g / mL, the concentration of 2-aminoterephthalic acid is 0.004 g / mL, and the volume ratio of acetic acid to deionized water is 1:

80.

3. The preparation method according to claim 2, characterized in that: The iron salt is ferric chloride hexahydrate, and the cobalt salt is cobalt nitrate hexahydrate.

4. The preparation method according to claim 1, characterized in that, The ZIF-8MOFs are prepared by dissolving 2-methylimidazole in methanol, adding zinc salt, stirring at room temperature, and centrifuging. The molar ratio of zinc salt to 2-methylimidazole is 1:3-6.

5. The preparation method according to claim 4, characterized in that: The zinc salt is zinc nitrate hexahydrate.

6. The preparation method according to claim 1, characterized in that, In step (2), the ratio of polyacrylonitrile, N,N-dimethylformamide, FeCo-MOFs and ZIF-8-MOFs is 0.15-0.25g: 3mL: 0.15-0.2g: 0.05-0.2g.

7. The preparation method according to claim 1, characterized in that: In step (3), the spinning voltage is 13-17kV and the distance from the spinning needle to the collecting copper mesh is 10-20cm.

8. The preparation method according to claim 1, characterized in that: In step (4), the inert gas used is nitrogen. The calcination is divided into two steps: first, the temperature is raised to 200-300℃ and kept at that temperature for 1-3 hours, and then the temperature is raised to 800-100℃ and kept at that temperature for 2-4 hours.

9. An iron-cobalt-doped porous carbon nanofiber prepared by the preparation method according to any one of claims 1 to 8.

10. The application of the iron-cobalt doped porous carbon nanofibers of claim 9 as a catalyst in the electrocatalytic oxygen reduction process.

Citation Information

Patent Citations

  • Multi-metal MOFs derived oxygen reduction / oxygen evolution double-function catalytic material, and preparation method thereof

    CN109926084A

  • Preparation method for rapidly growing metal organic framework derivative with assistance of metal salt

    CN113054207A